Rinsing tea reduces the health risk of neonicotinoids in the tea infusion - Shitao Hu; Yixiang Wang; Junjie Shao; Chengfeng Ying; Zongqi Hu; Haoyu Zhang; Yitian Xu; Xiaohui Sun; Quan Zhang (Environmental Chemistry and Ecotoxicology, 2025)
Neonicotinoid insecticides (neonics) are used extensively in agriculture because of its excellent insecticidal efficacy, yet its high-water solubility makes it susceptible to residues in water-based beverages such as tea infusions, posing a potential risk to public health. Nevertheless, the effects of rinsing as part of the Chinese tea ceremony on the residue of neonics in tea infusions have been rarely investigated. Herein, we collected 120 market-sourced tea samples which consisted of green tea, white tea, yellow tea, oolong tea, black tea, black tea and reprocessed tea (chrysanthemum tea, jasmine tea, clove tea and honeysuckle tea), and conducted multiple consecutive brews to analyze eight neonics. Neonics were detected in 97 % of the teas, with concentrations ranging from n.d. to 552.3 μg/kg. The residue was higher in green and chrysanthemum teas, with acetamiprid (ACE) being the predominant neonics, showing mean concentrations (μg/kg) of 250.9 ± 6.7 and 205.6 ± 46.2, respectively. In contrast, dark tea exhibited the lowest neonics residues. Rinsing tea before brewing appropriately reduced neonics residues and exposure risk, with exposure risk reduction levels ranging from 12.18 % to 37.42 %. This study suggests that tea consumption may be the primary route of neonic intake for most tea drinkers. Studies have shown that rinsing the tea leaves before brewing and restricting the brewing time (no more than one hour) can reduce neonics. This study highlights neonics residues, transfer rate during brewing, and potential health risks in tea and tea infusion.